ANTIBACTERICAL POTENCY OF CALCIUM HYDROXIDE AND PROPOLIS MIXTURE ON MIXED BACTERIA OF CARIOUS DENTIN - Ruslan Effendy; Vita Ariesta; Widya Saraswati (Conservative Dentistry Journal, 2019)
Background: Calcium hydroxide has been known as the gold standard of pulp capping process, but still has some weaknesses such as a pH that is too high to be potentially toxic, resistant to certain bacteria, causing necrosis of the pulp, and causing a tunnel defect. This weakness causes researchers to look for alternative ingredients that have antibacterical properties that can be combined with calcium hydroxide. Propolis has antibacterial properties such as flavonoids, tannins, saponins, and terpenoids which can work as the best carrier that allows dissociation of ions from calcium hydroxide so the combination of both that has antibacterial power is expected to have an effective antibacterial potency against the number of bacterial colonization with mixed dentine carious. Aims: This study aims to determine the antibacterial potency produced by a combination of calcium hydroxide and propolis against mixed bacteria of carious dentine. Methods: The research was carried out using 4 treatment groups with each of 7 samples. Group I is a combination of calcium hydroxide and propolis with a ratio of 1: 1, group 2 with a ratio of 1: 1.5, group 3 with a ratio of 1: 2, and a positive control group. Each sample was put into a suspense of mixed bacteria of carious dentine, grown for 24 hours. Suspense is vortexed for 1 minute so the solution becomes homogeneous. Put 0.1 ml of suspended mixed bacteria of dentine carious from BHIB media, grown for 24 hours on MHA media and counted the number of colonies. Results: The highest number of colonies in the positive control group, then group 1, group 2, and the least number of colonies in group 3 with the most extract of propolis. Conclusion: The combination of calcium hydroxide and propolis with a ratio of 1: 2 has the best antibacterial power in inhibiting colonization of mixed bacteria of carious dentine.